2006
DOI: 10.1152/ajplung.00449.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of endothelin-1-induced contraction in pulmonary arteries from chronically hypoxic rats

Abstract: Endothelin-1 (ET-1), a potent vasoconstrictor, is believed to contribute to the pathogenesis of hypoxic pulmonary hypertension. Previously we demonstrated that contraction induced by ET-1 in intrapulmonary arteries (IPA) from chronically hypoxic (CH) rats occurred independently of changes in intracellular Ca2+ concentration ([Ca2+]i), suggesting that ET-1 increased Ca2+ sensitivity. The mechanisms underlying this effect are unclear but could involve the activation of myosin light chain kinase, Rho kinase, PKC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
81
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 41 publications
(68 reference statements)
12
81
0
Order By: Relevance
“…Therefore, it is not possible, taking the present pharmacological approach, to distinguish indirect consequences of ROCK inhibitor-induced vasodilatation from limiting effects on other ROCK-mediated pathways. Other mechanisms, not explored in this study, by which ROCK inhibitors may have limited vascular remodeling include attenuated vascular production of endothelin-1 (27), inhibited downstream signaling of G-protein-coupled receptor ligands (11,28), and augmented function of the NO/ cyclic GMP pathway (29).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, it is not possible, taking the present pharmacological approach, to distinguish indirect consequences of ROCK inhibitor-induced vasodilatation from limiting effects on other ROCK-mediated pathways. Other mechanisms, not explored in this study, by which ROCK inhibitors may have limited vascular remodeling include attenuated vascular production of endothelin-1 (27), inhibited downstream signaling of G-protein-coupled receptor ligands (11,28), and augmented function of the NO/ cyclic GMP pathway (29).…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have implicated the RhoA/Rho-kinase (ROCK) pathway as central to the initiation and perpetuation of chronic PHT (5), based largely on the effects of two ROCK-specific kinase inhibitors: Y-27632 and fasudil (6). ROCK inhibitors have been reported to inhibit pulmonary artery myogenic responses in hypoxiaexposed adult rats (7) and fetal sheep (8) and to reverse sustained pulmonary vasoconstriction in response to hypoxia (9,10), bleomycin (10), or the infusion of vasoconstrictors, such as endothelin-1 (11). Systemic administration of ROCK inhibitors, commenced at the onset of injury, has been reported to prevent PHT induced either by hypoxia (9) or monocrotaline (12) in adult rodents.…”
mentioning
confidence: 99%
“…Findings that basal tone is elevated in pulmonary arterial rings from CH rats (34,54) and that vasodilators substantially lower pulmonary vascular resistance in CH rats acutely returned to a normoxic environment (34) provide further evidence that the vasoconstrictor response to CH is multifaceted and a primary determinant of pulmonary hypertension. Consistent with these findings, recent studies from our laboratory and others have identified an effect of CH on induction of myogenic tone in small pulmonary arteries (3) and enhancement of agonist-dependent vasoconstriction through a RhoA/ Rho kinase (ROCK)-mediated myofilament Ca 2ϩ sensitization pathway (14,20,34,54), responses that may contribute to the pathogenesis of pulmonary hypertension in this setting.…”
mentioning
confidence: 90%
“…Some studies demonstrated that acute anoxia could stimulate mRNA expression of vascular ET and its release (Weigand et al, 2006;Li et al, 2013). In the meantime, ET has the functions of promoting the proliferation of vascular smooth muscles and endothelial cells to further induce the changes in ultrastructures of vascular walls.…”
Section: Discussionmentioning
confidence: 99%